1993
DOI: 10.1093/nar/21.4.803
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sizing of individual fluorescently stained DNA fragments by flow cytometry

Abstract: Large, fluorescently stained restriction fragments of lambda phage DNA are sized by passing individual fragments through a focused continuous wave laser beam in an ultrasensitive flow cytometer at a rate of 60 fragments per second. The size of the fluorescence burst emitted by each stained DNA fragment, as it passes through the laser beam, is measured in one millisecond. One hundred sixty four seconds of fluorescence burst data allow linear sizing of DNA with an accuracy of better than two percent over a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 6 publications
4
104
0
1
Order By: Relevance
“…The mean RSD values associated with FCM and PFGE were 1.2% Ϯ 0.8% and 3% Ϯ 2%, respectively. These values are again in agreement with previously reported literature values (11,20,23,29,31,33). While the mean numerical precision of FCM was slightly better than that of PFGE, the two values were equivalent, within 1 standard deviation.…”
Section: Vol 42 2004 Assessment Of Flow Cytometry and Gel Electrophsupporting
confidence: 92%
See 2 more Smart Citations
“…The mean RSD values associated with FCM and PFGE were 1.2% Ϯ 0.8% and 3% Ϯ 2%, respectively. These values are again in agreement with previously reported literature values (11,20,23,29,31,33). While the mean numerical precision of FCM was slightly better than that of PFGE, the two values were equivalent, within 1 standard deviation.…”
Section: Vol 42 2004 Assessment Of Flow Cytometry and Gel Electrophsupporting
confidence: 92%
“…The largest observed error, for either method, was the underestimation of the 216.623-kb fragment by FCM (13% error). This discrepancy is noteworthy given the relatively accurate sizing of this fragment by PFGE (4.6% error) and the linear response of our FCM method in previous studies (20,29,31,33,39). In an attempt to understand this inconsistency, we examined the sequence of this 216-kb restriction fragment more closely.…”
Section: Vol 42 2004 Assessment Of Flow Cytometry and Gel Electrophmentioning
confidence: 92%
See 1 more Smart Citation
“…Currently, two strategies are feasible. In a flow system, a dilute solution of DNA is made to sequentially stream pass the detector [Goodwin et al, 1993]. The DNA dilution is such that most DNA molecules do not travel with any other DNA molecule and the time interval between two DNA molecules as they arrive at the detector is not too long.…”
Section: Physical Methods For Dna Separationmentioning
confidence: 99%
“…For small molecules and short exposure times (10 ms), we have found that can become comparable to w, and hence w does not serve as a good measure of the amount of DNA in a single restriction fragment. Therefore, we determined the relative lengths of restriction fragments by integrating the fitted function and using the proportionality between total fluorescence intensity and length (17). The absolute number of base pairs was determined by first calculating the relative lengths of the restriction fragments and then multiplying it by the known length of the DNA.…”
Section: [1]mentioning
confidence: 99%